Strategic Trade Policy Design with Asymmetric Information and Public Contracts - Brainard, S. Lael; Martimort, David (Review of Economic Studies, 1996)
This paper examines strategic trade policy under asymmetric information with publicly observable contracts. We analyse both the cases of unilateral and bilateral intervention. We find that the requirement of incentive compatibility undermines the strategic precommitment effect when public funds are costly, even with no restrictions on the form of the policies. Second, when firms sell substitute goods, the introduction of a rival interventionist government may reduce the cost of informational rents to each government. Third, it turns out that under bilateral intervention there exists a continuum of symmetric equilibria with levels of output and corresponding levels of welfare in the exporting countries which can be ranked. The requirement of ex post participation constraints for the firm limits the set of subsidies which can be offered to the firm. In particular, under bilateral intervention, the equilibrium levels of output which are implemented under adverse selection are below their values under ex ante uncertainty, i.e., below the equilibrium levels of output which are achieved when firms sign their contracts before the realization of their costs.